Choosing a Smuggler: Decision-making Amongst Migrants Smuggled to Europe - Campana, Paolo (European journal on criminal policy and research, 2021)
This paper explores how transactions between smugglers and migrants come about in the context of irregular migration. We first offer some theoretical reflections on the challenges that such a context poses to both parties—smugglers and migrants—and point to three main conditions under which smuggling transactions take place: illegality, asymmetrical information and low trust. Next, we explore the strategies that migrants and smugglers alike may employ to overcome these challenges. We focus on three broad sets of strategies related to information-gathering, to information-checking (reputation and the role of physical and virtual communities) and to developing substitutes for trust (guarantees, escrow services and hostage-taking strategies à la Thomas Schelling). To illustrate our reasoning, we draw on examples from published works as well as from a novel set of 43 qualitative interviews with migrants recently smuggled to Europe. Such interviews were carried out in a destination country (England) and in a transit country (Greece). Evidence from this work supports previous calls to move away from a simplistic “predator-victim” discourse.